Effect of aqueous fraction of Rosa damascena on ileum contractile response of guinea pigs - Dolati, Karim (Mashhad University of Medical Sciences, 2013)
Objective: The use of drugs with herbal origin is increasing for treatment of gastrointestinal (GI) disorders. Rosa damascena (R. damascena) is a well-known plant suggested to have beneficial effect on GI system. In this study, the effect of aqueous fraction of R. damascena on the contractions of isolated guinea pig ileum was investigated. Materials and Methods: Aqueous fraction of plant was obtained from ethanolic extract after ethyl acetate and n-butanol fractions were discarded. To evaluate effect of this fraction on ileum contraction, guinea pig ileum was removed and mounted on organ bath and its contraction was recorded. Effect of various concentrations (0.66, 0.83, and 1.3 mg/ml) of aqueous fraction on ileum contraction in comparison with Ach in presence and absence of atropine, a muscarinic antagonist of cholinergic, was evaluated. The response of ileum to 1 µg/ml of acetylcholine was considered as 100% response. Results: Our results showed that aqueous fractions of R. damascena dose-dependently increased basal guinea pigs ileum contractions (p<0.05 to p<0.001). Maximal contraction of fraction (1.3 mg/ml) induced 23.4 % of maximal Ach response. The contraction of ileum to aqueous fraction was significant decreased in presence 0.001 µg/ml of atropine. Conclusion: It is concluded that aqueous fraction of R. damascena has mild excitatory effect on ileum contraction and this fraction may be beneficial as a mild laxative agent.